The Predictive Value of Serum Calcium on Heart Rate Variability and Cardiac Function in Type 2 Diabetes Patients - Wang, Junyi; Xu, Zihui; Lv, Kang; Ye, Yingchun; Luo, Deng; Wan, Li; Zhou, Fen; Yu, Ailin; Wang, Shuo; Liu, Jingcheng; Gao, Ling (Frontiers in Endocrinology, 2022)
Background: Cardiovascular autonomic neuropathy (CAN) is common in patients with type 2 diabetes mellitus (T2DM), mainly presented as decreased heart rate variability (HRV) which often leads to cardiac death. However, HRV measurement is not convenient in most clinics. Therefore, identifying high risk patients for CAN in diabetes with easier measurements is crucial for early intervention and prevention of catastrophic consequences. Methods: In this cross-sectional study, 675 T2DM patients with normocalcemia were selected. Of these, they were divided into two groups: normal HRV group (n=425, 100 ms≤ SDNN ≤180 ms) vs. declined HRV group (n =361, SDNN <100ms). All patients’ clinical data were collected and the correlation of clinical variables with HRV were analyzed by correlation and logistic regression analysis. The area below the ROC curve was used to evaluate the predictive performance of serum calcium on HRV. Results: In this study, declines in HRV was present in 37.0% of T2DM patients. Significant differences in albumin-adjusted serum calcium levels (CaA) (8.86 ± 0.27 vs. 9.13 ± 0.39 mg/dl, P <0.001) and E/A (0.78 ± 0.22 vs. 0.83 ± 0.26 mg/dl, P =0.029) were observed between declined HRV and normal HRV groups. Bivariate linear correlation analysis showed that CaA and E/A were positively correlated with HRV parameters including SDNN (P <0.001), SDNN index (P <0.001), and triangle index (P <0.05). The AUC in ROC curve for the prediction of CaA on HRV was 0.730 (95% CI (0.750–0.815), P <0.001). The cut-off value of CaA was 8.87 mg/dl (sensitivity 0.644, specificity 0.814). The T2DM patients with CaA <8.87 mg/dl had significantly lower HRV parameters (SDNN, SDNN index, rMSSD and triangle index) than those with CaA ≥8.87 mg/dl (P <0.01, respectively). Multivariate logistic regression analysis showed significantly increased risk of declined HRV in subjects with CaA level <8.87 mg/dl [OR (95% CI), 0.049 (0.024 - 0.099), P <0.001]. Conclusions: Declined HRV is associated with lower CaA level and worse cardiac function. Serum calcium level can be used for risk evaluation of declined HRV in T2DM patients even within normocalcemic range.